Assimilation via Prices or Quantities? : Labor Market Institutions and Immigrant Earnings Growth in Australia, Canada and the United States - Heather Antecol; Peter Kuhn; Stephen J. Trejo (Claremont McKenna College, Department of Economics, 2004)
How do international differences in labor market institutions affect the nature of immigrant earnings assimilation? Using 1980/81 and 1990/91 cross-sections of census data from Australia, Canada, and the United States, we estimate the separate effects of arrival cohort and duration of destination-country residence on immigrant outcomes in each country. Relatively inflexible wages and generous unemployment insurance in Australia suggest that immigrants there might improve themselves primarily through employment gains rather than wage growth, and we find empirically that employment gains explain all of the labor market progress experienced by Australian immigrants. Wages are less rigid in Canada and the United States than in Australia, with the general consensus that the U.S. labor market is the most flexible of the three. We find that wage assimilation is an important source of immigrant earnings growth in both Canada and the United States, but the magnitude of wage assimilation is substantially larger in the United States. These same general patterns remain when we replicate our analyses for two subsamples of immigrants - Europeans and Asians - that are more homogeneous in national origins yet still provide sufficiently large sample sizes for each country.
Keywords: 330; Migranten; Ausländische Arbeitskräfte; Lohn; Soziale Integration; Arbeitsmarktflexibilisierung; Schätzung; Australien; Kanada; Vereinigte Staaten